Producer Prices in the Transition to a Common Currency - Niclas Andrén; Lars Oxelheim (Research Institute of Industrial Economics (IFN), 2006)
We analyze producer price developments in the transition from a national exchange rate regime to a monetary union. The focus is on the European Economic and Monetary Union (EMU). Stylized facts witness about an exploding gaps in producer-price inflation during the years immediately following the completion of the EMU. Price convergence is found to be an important driver throughout the entire euro period (1999-2005), but with no significant differences in speed compared to the pre euro period. Productivity growth had its primary effect in the first years and effective exchange-rate changes in the later years of the euro period.
Keywords: E31; E44; F15; F23; G34; 330; Producer prices; Relative prices; Price convergence; Euro; Balassa-Samuelson; Betriebliche Preispolitik; Relativer Preis; Preiskonvergenz; Preisrigidität; Eurozone; Euro; EU-Staaten